Improving Human Resources Management Services At Vivetato Langga Payung, Labuhanbatu Selatan - Olin Sarita Nasution; Aziddin Harahap; Abd Halim (PT Mattawang Mediatama Solution, 2023)
The role of human resource management is very influential in improving employee service at Vivetato Langga Payung, South Labuhanbatu. Apart from that, from the role of human resource management, it can be seen how much the employees are doing the job and are competent in the fields contained in the vivetato.This study aims to examine human resources that are very influential in the scope of Vivetato Langga Payung, South Labuhanbatu. The level of service of employees is very influential on the interest of consumers. Human resources are influential in improving services at Vivetato Langga Payung, South Labuhanbatu to consumers.The research design uses a qualitative test and is a survey and interview research. The population of all Vivetato Langga Payung Labuhanbatu Selatan employees is 6 people with qualitative data analysis.The results of the study show that human resources have a significant effect on the scope of Vivetato Langga Payung, South Labuhanbatu. Human resources have a significant effect on improving services at Vivetato Langga Payung Labuhanbatu Selatan. take the umbrella of South Labuhanbatu